Analisis Swot Pengembangan Kawasan Wisata Telaga Ngebel Di Kabupaten Ponorogo - Imron, Muhammad (JURNAL EKOMAKS : Jurnal Manajemen, Ekonomi Kreatif dan Bisnis, 2020)
The development of tourist areas is directed as a mainstay sector to boost economic growth, increase local revenues, empower the economy of the community, expand employment and increase the introduction and marketing of typical tourism areas. Ngebel Lake is a natural lake located in District Ngebel, Ponorogo Regency which has a stunning natural scenery with the condition is still natural, save a million potential to be developed. Development of Ngebel Lake tourism area should be planned thoroughly and use appropriate strategies in order to obtain optimal benefits for the community. The objectives of this research are: 1) to analyze the condition of external factors including opportunities and threats, 2) to analyze the condition of internal factors including strengths and weaknesses, appropriate for the development of tourism area Ngebel Lake using SWOT Analysis. Based on SWOT analysis, Telaga Ngebel tourism area has an external opportunity as well as an enormous internal strength to be developed. Result of internal and external matrix (IE), hence alternative of appropriate strategy to develop tourist area of Telaga Ngebel is SO Strategy (Strenght-Opportunity) that is a strategy chosen by using strength to utilize or seize opportunity. Implementation of the strategy is done through the development of tourism products, market development and market penetration. Important policies need to be taken, such as improving road infrastructure, developing tourism products, promoting promotion, providing souvenir shop area, handicraft and food, providing street lighting, improving hygiene and waste handling and cooperating with various parties including investors.Â Keywordsâ€”: strengths; weaknesses; opportunities; threats; development.